POTENSI BIOLARVASIDA EKSTRAK HERBA Ageratum conyzoides Linn. dan DAUN Saccopetalum horsfieldii Benn. TERHADAP LARVA NYAMUK Aedes aegypti L. - Noer Moehammadi (The East Java Biological Society, 2005)
The purpose of this research was to compare potential biolarvasida lethal concentration from extractherba Ageratum conyzoides and leaves Saccopetalum harsfieldii to larva aegypti. This research used the experimental methods with completely random design. With two test, preliminary bioassay and real bioassay. After preliminary bioassay was done, real bioassay was done by determining 8 concentration of leaves extract Saccopetalum horsfieldii, which were: 300 ppm, 600 ppm, 1200 ppm, 2000 ppm, 3000 ppm, 3500 ppm, 5000 ppm, 6000 ppm, and 1 control. For sample extract Ageratum conyzoides were: 750 ppm, 1500 ppm, 2000 ppm, 2500 ppm, 3000 ppm, 4000 ppm, and 1 control. Each treatment was replied five times. In order to know LC 90 from leaves extract of S. horsfieldii and herbs extract of Ageratum conyzoides probit analysis was used. The result of this research indicated extract herbal Ageratum conyzoides is more toxic compare with extract Saccopetalum horsfieldii leaves, this case identified by value LC 90 Ageratum conyzoides more lower than LC 90 Saccopetalum horsfieldii.